HUBUNGAN SUMBER DAYA PENGHIDUPAN, PRINSIP AGROEKOLOGI, DAN PENERIMAAN AGROFORESTRI PADA PETANI KOPI HUTAN KEMASYARAKATAN KABUPATEN LEBONG PROVINSI BENGKULU - Yura Farizki; Septri Widiono; Bembi Akbar Serawai; Anggita Tresliyana Suryana (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
The coffee agroforestry system in the Bukit Daun Community Forest (HKm), Lebong Regency, integrates conservation functions and the improvement of community economy. This study aims to analyze the condition of livelihood resources, the application of agroecology, the structure of agroforestry income, and the relationships between variables. The study sample consisted of 182 respondents using proportional random sampling techniques. Analysis was conducted using a 0–1 scale index (Min-Max Scaling), descriptive income analysis, and SEM-PLS. The results show that livelihood resources are in the moderate category, with the highest index in natural capital (0.516), followed by financial (0.507), social (0.455), physical (0.418), and human (0.316). The application of agroecology is fairly good in biological synergy (0.747) and biomass recycling (0.632), but low in biodiversity (0.206). The income structure is dominated by main crops at 87%, while intercropped plants make up 13%. SEM-PLS results indicate that agroecology is influenced by natural capital, financial, and social, whereas acceptance is influenced by social, human, financial, and physical capital.